Penile fracture. Is it the management problem for the urologist in the rural? - Prawito Singodimejo, Prawito Singodimejo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2005)
Fracture of the penis is a rupture of the corpus cavernosum due to blunt trauma. In the West the penile fracture is commonly resulted from trauma in sexual intercourse but in the Middle East and Mediterranean is predominantly due to masturbation. The other causes are unconscious nocturnal manipulation or fall onto the erecting penis.Â We present a penile fracture case, one of the less frequent urological traumas, referred to the SardjitoÂ Hospital. The report illustrated a 23 year old circumcised male, who had suffered from penile fracture while his penis was erecting. He was referred to the hospital by a general practitioner two days after the incident. Immediate surgical repair was done with the indication of specific history and severe hematoma in the penis as the clinical presentations. The patient was discharged on day 8 postoperation. A mild hematom was present in the wound and no sign of infection.Discussion about penile fracture written in the literature by authors is presented.Key words: penile fracture, causes, urologist problem, surgical repair.Â